Empathy Dysfunction and Risk Factors for Brawl and Klithih Behavior among Muslim High School Students in Yogyakarta City - Tri Sutanti; Uman Suherman; Ilfiandra Ilfiandra; Nurul Hidayati Rofiah (Pamomong: Journal of Islamic Educational Counseling, 2025)
This study aimed to examine empathy profiles and empathy dysfunction among Muslim adolescents involved in brawl and klithih behavior in Yogyakarta City high schools and to identify factors underlying their involvement. The research used a descriptive design combining quantitative and qualitative data. Participants were seven Muslim students from private high schools selected through purposive sampling. Data were collected using an empathy scale and in-depth interviews. Quantitative data were analyzed descriptively using measures of central tendency and dispersion, whereas qualitative data were examined using Miles and Huberman’s model of data reduction, display, and conclusion drawing. The findings indicate that involvement in brawls and klithih is closely associated with empathy dysfunction, which is exacerbated by low emotional regulation and unsupportive family backgrounds. These results inform guidance and counseling services and can guide strategies to develop adaptive empathy among students at risk of violent behavior. The study enriches empirical understanding of adolescent empathy and school violence. This study has limitations in geographical scope, being restricted to Yogyakarta City schools, so the findings may not generalize to adolescents in regions with different sociocultural contexts. The study also focused mainly on individual factors, while external influences such as social environments, educational systems, and institutional roles were not systematically explored. Future research should broaden the participant context across diverse regions and deepen the analysis of structural dimensions that contribute to empathy dysfunction and youth violence. Future studies should also use participatory approaches involving students, teachers, and school communities to build a more holistic and applicable understanding.